A soft–hard template approach towards hollow mesoporous silica nanoparticles with rough surfaces for controlled drug delivery and protein adsorption. Issue 31 (21st August 2015) - Zhang, Haijiao; Xu, Huijuan; Wu, Minghong; Zhong, Yufang; Wang, Donghai; Jiao, Zheng
<x xml:space="preserve">Abstract</x> Novel hollow mesoporous silica nanoparticles (HMSNs) with rough surfaces have been successfully prepared using a facile soft–hard template route.